Erratum: Study of sexual dimorphism of Malaysian crania: An important step in identification of the skeletal remains [Anat Cell Biol. 50, 2 (2017) (86-92)] DOI:10.5115/acb.2017.50.2.86 - Ibrahim A.; Alias A.; Nor F.M.; Swarhib M.; Bakar S.N.A.; Das S.; Abdullah N.; Noor M.H.M. (Korean Association of Anatomists, 2024)
Indexed by SCOPUS/ERA